PUBLIC KNOWLEDGE OF HALAL FOOD IN THE GLOBAL MARKET - Sharil, Suhaila; Wan Mahmud Khairi, Wan Ahsani Fadhilah; Satari, Hisam; Asmadi, Athira Ayuni (Journal of Human Capital Development (JHCD), 2025)
ABSTRACT Halal food is food that is pure and wholesome, and that meets the standards of quality and safety that Islam teaches for self-care and mental well-being. For instance, food processing that involves contact with faeces (najis) violates the halal criteria. Halal food also requires that there is no contamination or impurity at any stage of its production, storage, cooking, refining, transportation, or handling of raw materials, in accordance with the Islamic perspective. The aim of this study is to evaluate the level of awareness and knowledge of halal food among the global consumers. This study was carried out using quantitative methods, namely through the method of survey by giving questionnaire forms to 115 respondents. The results of the study were analyzed descriptively and found that public knowledge of halal food in the global market is simplistic with a minimum value of 3.7, namely that food that has the Malaysian halal logo is safe and halal to eat and the establishment of global halal standards is very necessary to avoid misunderstandings, mistakes, misuse of halal certificates and losses for entrepreneurs. Keywords: public knowledge, halal food, global market